1984
DOI: 10.1016/0003-9861(84)90125-5
|View full text |Cite
|
Sign up to set email alerts
|

A structural comparison of the A and B subunits of Griffonia simplicifolia I isolectins

Abstract: A structural comparison between the A and B subunits of the five tetrameric Griffonia simplicifolia I isolectins (A4, A3B, A2B2, AB3, B4) was undertaken to determine the extent of homology between the subunits. The first 25 N-terminal amino acids of both A and B subunits were determined following the enzymatic removal of N-terminal pyroglutamate blocking groups with pyroglutamate aminopeptidase. Although 21 amino acids were common to both subunits, there were four unique amino acids in the N-terminal sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…The GS-4 structure (PDB code 1gsl; Delbaere et al, 1993) produced the best results. Although the sequencing of GS-1-B 4 is in progress, a BLAST (Altschul et al, 1990) alignment of the N-terminal GS-1-B 4 sequence (Lamb & Goldstein, 1984) showed a 44% identity with that of GS-4. The initial cross-rotation search (DeLano & Bru È nger, 1995) gave a solution with a rotation function value of 0.0657 at 4 = 0.25 at 1 = 334, 2 = 78, 3 = 278 .…”
Section: Figurementioning
confidence: 99%
“…The GS-4 structure (PDB code 1gsl; Delbaere et al, 1993) produced the best results. Although the sequencing of GS-1-B 4 is in progress, a BLAST (Altschul et al, 1990) alignment of the N-terminal GS-1-B 4 sequence (Lamb & Goldstein, 1984) showed a 44% identity with that of GS-4. The initial cross-rotation search (DeLano & Bru È nger, 1995) gave a solution with a rotation function value of 0.0657 at 4 = 0.25 at 1 = 334, 2 = 78, 3 = 278 .…”
Section: Figurementioning
confidence: 99%
“…West and Cope likewise noted the neuraminidaseengendered GS-I reactivity of endometrial epithelia (25) and results shown in their report were consistent with the present ones. GS-I is a tetramer and there are two types of subunit, A and B (14). Commercially available GS-I consist of A4 or B4, or might be any combination of A and B subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse Transcription-PCR and cDNA Cloning of G. simplicifolia GS I-A and GS I-B Isoforms-PCR was used to amplify the coding region of GS I-A and GS I-B isoforms using degenerate primers that were designed with regard to N-terminal peptides, previously characterized for both isoforms (11), and conserved internal peptide regions deduced from the multialignment of the whole protein family. Total RNA was obtained by grinding G. simplicifolia seeds in liquid nitrogen followed by an extraction using TRIzol reagent (Sigma Chemical Co.) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing of the 25 N-terminal amino acids of the A and B subunits demonstrated 4 different residues and tryptic peptide mapping showed that ϳ30% of the peptides are common to both lectins (11). Thus, the GS I lectins appear to be excellent models to study the molecular basis for recognition of Gal versus GalNAc monosaccharides.…”
mentioning
confidence: 99%